2012
DOI: 10.1111/bjd.12044
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of discoid lupus erythematosus

Abstract: The present study provides new insights into the dermoscopic variability of DLE located on the face, trunk and extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
80
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 8 publications
14
80
4
1
Order By: Relevance
“…Large, yellow-brown dots correspond to keratotic plugs in the dilated follicular ostia [3,2]. Longstanding, inactive lesions show absence of follicular openings and cicatricial milky red or white patches and structureless white and brown areas [3,6,7]. Thick arborizing, monstrous vessels may be noticed too [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large, yellow-brown dots correspond to keratotic plugs in the dilated follicular ostia [3,2]. Longstanding, inactive lesions show absence of follicular openings and cicatricial milky red or white patches and structureless white and brown areas [3,6,7]. Thick arborizing, monstrous vessels may be noticed too [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings can be observed in the pathology of DLE lesions, such as those presented in Figure 2. The structureless, white areas described in end-stage lesions of DLE are different because they correspond histologically to diffuse dermal fibrosis [7]. …”
Section: Discussionmentioning
confidence: 99%
“…SD was reported to exhibit dotted vessels with a patchy distribution and yellow scales and, consequently, discrimination between facial psoriasis and SD might be enhanced by the assessment of the scale color, similarly to other body sites [10]. Rosacea, granulomatous disorders and discoid lupus erythematosus display characteristic dermoscopic criteria that facilitate their diagnosis, namely polygonal vessels, yellow-orange patches and follicular disturbances, respectively [10,14,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, several studies have shown that dermoscopy may be a useful tool to assist the non-invasive diagnosis of various inflammatory skin diseases [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] , including classic GA [20][21][22][23][24] . Indeed, albeit dermoscopic examination of this dermatosis has been reported to show heterogeneous findings, the use of such a technique may come in handy to support the distinction from its main differential diagnoses as they typically show a different appearance [20][21][22][23][24] .…”
mentioning
confidence: 99%